Properties And Characterization Of Lignin Nanoparticles Reinforced Biopolymer Films - Alfatah, Tata (2023)
This study presents a new, constructive, essential, and critical idea for the fabrication of biopolymer films from a red seaweed matrix (Kappaphycus alvarezii) with the incorporation of lignin nanoparticles (LNPs). Globally, various environmental issues are already attributed to petroleum-based plastic pollution, which is majorly consumed by packaging applications. On the other hand, the development of biopolymer materials that are bio-based and/or degradable is commonly presented as an alleviating alternative, offering sustainable and eco-friendly properties over conventional petroleum-derived plastics. However, the hydrophilicity, poor water barrier, low mechanical, and weak antimicrobial properties of biopolymer films have hindered their utilization in packaging applications. Kappaphycus alvarezii is no exception to these challenges of biopolymer films. In this study, lignin nanoparticles (LNPs) with a purification process were used in different loadings as enhancements in a Kappaphycus alvarezii matrix to reduce the hydrophilic nature and improve antibacterial properties of the matrix and compared with unpurified LNPs. The nanofiller was generated using an environmentally friendly method from an oil palm (Elaeis guineensis) empty fruit bunch (EFB) black liquor of soda pulping waste via acid precipitation technique.